Pap smear screening, pap smear abnormalities and psychosocial risk factors among women in a residential alcohol and drug rehabilitation facility. (17th August 2015) - Soccio, Jacqui; Brown, Margaret; Comino, Elizabeth; Friesen, Emma
Abstract: Aim: To compare rates of late‐ screening, abnormal Pap smears and prevalence of psychosocial factors for cervical cancer between women in the community and women attending a residential drug and alcohol facility. Background: Women with drug and alcohol addiction experience higher rates of abnormal Pap smears, late‐ or under‐ screening and psychosocial risk factors including domestic violence and sexual assault. Design: A descriptive cross‐sectional study of women attending publically funded women's health clinics in the community or in a live‐in residential drug and alcohol rehabilitation facility. Methods: The study was approved in May 2012. Data were collected between October 2012–December 2013 using standardized women's health questionnaires, domestic violence screening tools and Pap smear tests. Results: Women attending the rehabilitation facility had higher rates of abnormal Pap smears (16·7% vs. 1·6%) and self‐reported history of abnormal Pap smears (44·4% vs. 20·6%). They also reported higher rates of smoking (72·2% vs. 29·2%), experience of sexual assault (44·1% vs. 16·9%), experience of domestic violence (65·7% vs. 10·9%) and other psychosocial risk factors, than women living in the general community. Unexpectedly, women in the rehabilitation facility reported similar levels of late screening as women in the community (52·8% vs. 55·4%). Conclusion: Women with drug and alcohol addiction have significantly higher incidence of risk factors for cervical cancer and abnormal Pap smears. Provision of opportunistic cervical cancer screening during residential treatment appears to reduce incidence of late‐screening. Roles of Women's Health Nurses in providing services to vulnerable women should be explored further.